Pengembangan Sistem Informasi Penerimaan Mahasiswa Baru di Universitas Nusantara PGRI Kediri: Indonesia - Kamba, Enos Bungsenior; Firliana, Rina; Harini, Dwi (Nusantara of Engineering (NOE), 2022)
This research is motivated by the process of accepting new students at Nusantara University PGRI Kediri which aims to develop an information system on the PMB website that is more complete and meets the needs of prospective new students and admin promotions at Nusantara University PGRI Kediri. This admission technique still has shortcomings which then make prospective new student participants unable to obtain information optimally with the required needs where prospective students who have filled out the form and have saved the data, cannot re-edit the data, there is no icon/symbol that can be used to re-edit the data. print data stating the status of the registrant/participant, as well as the report on the recapitulation of the total number of prospective students and study programs are not yet available in the system. The conclusion of this study is that the information system related to data collection of prospective new students has been in accordance with the plan as evidenced by the acquisition of the results of system testing. The development of this system will make it easier for prospective students to perform data management. In addition, this can also help the administration in managing data for prospective students. Based on the conclusions of this study, it is recommended that the main objective of "Development of New Student Admission Information System at Nusantara University PGRI Kediri" is to develop an information system on the PMB website that is more complete and meets the needs of prospective new students and promotion admins at Nusantara University PGRI Kediri.Keywords: System Development, New Student Admission